Proper Validation of Freezing Prediction Results from Process Simulation - Intan Ellina binti Norazmi, Intan Ellina (Universiti Teknologi Petronas, 2012)
The motivation of the work is to increase the knowledge about thermodynamic modeling of freeze outs in natural gas systems and a deeper understanding of the phase behavior of natural gas mixtures, due to the problems experienced in cryogenic natural gas process-plants. Critical components in natural gas mixtures introduce a risk of forming a solid coating and plugging the process equipment. Hence, it is relevant to examine methane rich binary mixtures containing components with high risk of freezing. Due to their high triple point temperatures, carbon dioxide, benzene and cyclohexane are regarded as the most critical components. Due to time constraint, the scope of study is narrowed down to methane rich binary mixture with carbon dioxide as the main critical component. This study was carried out by applying a simulation tool called HYSYS, where the equation of state method which is the Soave-Redlich-Kwong equation is implemented. To investigate the reliability and accuracy of the equation of state method, experimental data from the literature is used as a foundation for validation. The outcome is that the BIAS and average absolute deviation (AAD) of all three papers under study is within the satisfying degree of accuracy. Thus it validate that the data from simulation is reliable and is able to reduce the dependency of experimental procedure that is more costly.